Des premières priorités, un hasard imprévu, applaudir des deux mains, découvrir pour la première fois… Or about Pleonastic Phrasemes in Contemporary French and Polish - Izert, Małgorzata (Verbum, 2024)
In this article, we present a comparative study of approximately hundred pleonastic collocational phrasemes in French, created through three specific syntactic patterns: N+Adj / Adj+N or N de/à N and V+Adv, and their Polish equivalents. We attempt to explain the semantic mechanisms of pleonasm construction. Some of these pleonasms are due to the speakers' ignorance or thoughtlessness, making them incorrect and to be avoided in official language. Others are intentional and useful, as they add additional value such as emphasis or intensity, precision and explanation to the meaning of the constructed phrasemes. The componential analysis we propose as a method of analysis, demonstrates either a semantic congruence, that is a useful correlation between the sememes of the components of pleonastic phrasemes, or excessive and useless addition. In other words, it allows us to verify whether the redundancy of meaning has any utility or is perfectly superfluous.
Keywords: collocational phraseme; contrastive analysis; intensity; pleonasm; repeating